The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1517/14656566.2015.1067679
|View full text |Cite
|
Sign up to set email alerts
|

Advances in pharmacotherapy for wet age-related macular degeneration

Abstract: Although anti-VEGF drugs have shown mild-term good efficacy and safety profile in the treatment of neovascular AMD, they are far away from being a perfect therapy. Pharmacological research should focus on finding new molecular targets in the AMD pathogenetical pathway and on developing longer lasting agents or new drug delivery systems. Besides the development of new drugs, a better characterization of patients is also needed, taking into account variables such as choroidal neovascularization subtypes and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 70 publications
0
16
0
1
Order By: Relevance
“…Clinical manifestations of neovascular AMD include accumulation of retinal, subretinal and sub-RPE fluid. If left untreated, neovascular AMD will typically result in severe vision loss [88,89]. …”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…Clinical manifestations of neovascular AMD include accumulation of retinal, subretinal and sub-RPE fluid. If left untreated, neovascular AMD will typically result in severe vision loss [88,89]. …”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…The efficacy of anti-VEGF therapy, already widely demonstrated in in-vitro and in-vivo studies, showed fewer efficacies in real life studies than in clinical trials [19]. In recent years, many efforts were computed to find new drugs that can overcome the effectiveness of those available in the AMD therapy [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies showed their effectiveness in improving vision function and reducing macular edema. Nevertheless, intravitreal injection of corticosteroids carries significant complication risk such as cataract progression, ocular hypertension and endophthalmitis [18][19][20]. Thus, retro bulbar injections of corticosteroids are a valid alternative to intravitreal injection: it has been demonstrated to provide the same effectiveness in reducing macular edema but with a lower rate of intraocular complications [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 10 years, several pharmacological therapies targeting VEGF have been approved for the treatment of CNV secondary to AMD. Currently, two commonly used anti-VEGF drugs (ranibizumab and aflibercept) have been approved for the intravitreal treatment of neovascular AMD by the US FDA and the European Medicines Agency, while bevacizumab, an additional anti-VEGF drug developed for systemic use, is commonly used intravitreally in an off-label fashion in many countries [11]. Bevacizumab, the first anti-VEGF agent used to treat CNV [12], is a humanized full-length monoclonal antibody that has been shown to be effective in preventing visual loss and capable of significantly improving visual acuity in AMD patients with subfoveal CNV [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%